Emotional reactions of peers influence decisions about fairness in adolescence - Klapwijk, Eduard T.; Peters, Sabine; Vermeiren, Robert R.; Lelieveld, Gert-Jan (Frontiers in Human Neuroscience, 2013)
During adolescence, peers take on increasing importance, while social skills are still developing. However, how emotions of peers influence social decisions during that age period is insufficiently known. We therefore examined the effects of three different emotional responses (anger, disappointment, happiness) on decisions about fairness in a sample of 156 adolescents aged 12 to 17 years. Participants received written emotional responses from peers in a version of the Dictator Game to a previous unfair offer. Adolescents reacted with more generous offers after disappointed reactions compared to angry and happy reactions. Additionally, we found preliminary evidence for developmental differences over adolescence, since older adolescents differentiated more between the three emotions than younger adolescents. In addition, individual differences in social value orientation played a role in decisions after happy reactions of peers to a previous unfair offer, such that participants with a ‘proself’ orientation made more unfair offers to happy peers than ‘prosocial’ participants. Taken together, our findings demonstrate that adolescents take emotions of peers into account when making social decisions, while individual differences in social value orientation affect these decisions, and age seems to influence the nature of the reaction.